Two additional new species of Sphaerodactylus (Reptilia, Squamata, Gekkonoidea, Sphaerodactylidae) from the Honduran Bay Islands - Mccranie, James R.; Hedges, S. Blair (Zootaxa, 2013)
Recently, we described two new species of geckos of the genus Sphaerodactylus from the Bay Islands of Honduras. After further collections, and morphological and molecular analyses, we describe two additional species here. One of the new species belongs to the S. millepunctatus species group, which is centered in Middle America. The other new species belongs to the S. copei species group, which is centered in the Greater Antilles.